KEPUTUSAN PEMBELIAN DITINJAU DARI GAYA HIDUP, CITRA MEREK, DAN KUALITAS PELAYANAN PADA POINT COFFEE DI SURAKARTA ( STUDI PADA GENERASI Z DI SURAKARTA ) - Talva, Tursia Danisa Sajita; Mursito, Bambang; Widayanti, Rochmi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The aim of this research is to see the influence of Lifestyle, Brand Image and Service Quality on purchasing decisions at Point Coffee in Surakarta (Study of Generation Z in Surakarta). This research uses a questionnaire as a data collection tool while for the population itself the research selects generation Z in Surakarta who have purchased an infinite number of Point Coffee products in Surakarta. The sample for this research was 108 respondents. Sample determination was carried out using purposive sampling technique. The data analysis technique was carried out using SmartPLS. The results of the research show that Lifestyle, Brand Image, and Service Quality are able to influence Point Coffee Purchasing Decisions in Surakarta among Generation Z in Surakarta positively and significantly, either partially or simultaneously.